PARENTS’ ROLE IN ASSISTING CHILDREN IN ONLINE LEARNING DURING COVID19 PANDEMIC - Ririk Woro Hapsari; Sekar Dwi Ardianti; Erik Aditia Ismaya (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The Covid-19 pandemic has affected the education sector; as a result, the government has made policies to conduct distance learning or known as online learning. In online learning, parents have double roles, as a parent and as a teacher, to assist children in online learning during Covid-19 pandemic. Lack of understanding of the importance of assisting children during online learning causes parents to pay less attention to their role in assisting children during online learning. The aim of this research was to know parents’ roles to assist children in online learning during Covid-19 pandemic. This research utilized qualitative methods with the type of case study. This research was conducted in Desa Temulus, Kecamatan Mejobo, Kabupaten Kudus, involving 5 parents and 5 children. The children attended learning at SD 1 Temulus, and both children and their parents lived in the researchers’ environment. Data were collected through observation, interviews, and documentation. This research applied a descriptive qualitative data analysis with triangulation methods to validate the data. The steps of data analysis were data reduction, data presentation, and making conclusion. The results of this research revealed that parents played several roles in online learning during the Covid-19 pandemic; they were: a) as caregivers and educators; b) as mentors; c) as motivators; and d) as facilitators. Therefore, parents should provide time and attention in assisting their children to learn during online learning.